Collaborative Translation in the English/Spanish Classroom - Rich, Dana (My University, 2015)
The purpose of this project was to identify an effective method to teach and evaluate a college course for English/Spanish translation.
Color poster with text, photographs, charts, and graphs.
Keywords: English-Spanish translation; Translation; Language classes; Posters